2020
DOI: 10.1080/02713683.2020.1826977
|View full text |Cite
|
Sign up to set email alerts
|

Macro- and Microscale Properties of the Vitreous Humor to Inform Substitute Design and Intravitreal Biotransport

Abstract: Research on the vitreous humor and development of hydrogel vitreous substitutes have gained a rapid increase in interest within the past two decades. However, the properties of the vitreous humor and vitreous substitutes have yet to be consolidated. In this paper, the mechanical properties of the vitreous humor and hydrogel vitreous substitutes were systematically reviewed. The number of publications on the vitreous humor and vitreous substitutes over the years, as well as their respective testing conditions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 180 publications
(277 reference statements)
1
17
0
Order By: Relevance
“…Other Authors reported that the physiological concentration of Vitamin C in the lens is 1 -2 mM (0.174 -0.348 g) [28], The fact that there was no significant difference in the levels of Vitamin C found in the two groups underscores the need for supplementation in both elderly and diabetic Nigerian populations. A study which analysed antioxidant markers such as catalase, Cu-Zn superoxide dismutase in these two groups found diabetic patients having significantly lower levels than their non-diabetic counterparts and proposed that elevated glucose levels might be involved in the insufficient production of antioxidant enzymatic activ-ity [29].…”
Section: Discussionmentioning
confidence: 78%
“…Other Authors reported that the physiological concentration of Vitamin C in the lens is 1 -2 mM (0.174 -0.348 g) [28], The fact that there was no significant difference in the levels of Vitamin C found in the two groups underscores the need for supplementation in both elderly and diabetic Nigerian populations. A study which analysed antioxidant markers such as catalase, Cu-Zn superoxide dismutase in these two groups found diabetic patients having significantly lower levels than their non-diabetic counterparts and proposed that elevated glucose levels might be involved in the insufficient production of antioxidant enzymatic activ-ity [29].…”
Section: Discussionmentioning
confidence: 78%
“…An ideal vitreous substitute should be based on the viscoelastic properties of the natural, juvenile and healthy human vitreous (10 Pa). In contrast, a majority of the previously proposed vitreous substitutes have stiffnesses that are orders of magnitude higher than those of the reported human vitreous body, reviewed by Tram et al [13], and may thus cause mechanical damage to the surrounding tissue.…”
Section: Requirements For Vitreous Substitutesmentioning
confidence: 90%
“…Recent tamponade strategies therefore aim at hydrophilic, hydrogelbased systems because of their favourable properties such as high water content, optical transparency, suitable refractive indices and densities, adjustable rheological properties, injectability, biocompatibility and their ability to tamponade the retina via viscosity and swelling pressure. Recent reviews affirm the relevance and need for new vitreous replacement strategies [8][9][10][11][12][13]. The following review will provide an update on new vitreous substitutes with a focus on polymer-based systems (for systematic literature review see Supplementary Information, http://links.lww.com/COOP/A39).…”
Section: Introductionmentioning
confidence: 99%
“…The VH is important for the structural integrity of the eye as well as in nutrient and oxygen trafficking to other avascular structures of the eye. 26,27 Therefore, the VH coordinates eye growth and provides support to the retina. 28 Due to the VH's proximity to the retina and avascular nature, pathological changes of the retina are often reflected in the VH.…”
Section: Biofluids For Diabetic Retinopathy Analysismentioning
confidence: 99%